Males perceive honest information from female released sex pheromone in a moth. (13th July 2021) - Gonzalez-Karlsson, Adrea; Golov, Yftach; Steinitz, Hadass; Moncaz, Aviad; Halon, Eyal; Horowitz, A Rami; Goldenberg, Inna; Gurka, Roi; Liberzon, Alexander; Soroker, Victoria; Jurenka, Russell; Harari, Ally R
Abstract: There is accumulating evidence that male insects advertise their quality to conspecific females through pheromones. However, most studies of female released sex pheromone assume information transfer regarding merely the species of the female and her mating status. We show that more information is conveyed through the female sex pheromone, positioning it as an honest sexual trait. We demonstrate that females in bad physical conditions (small, starved, or old) lay significantly fewer eggs than females in good conditions (large, fed, or young). The ratio of components in the sex pheromone blend in gland extracts of the female pink bollworm moths provided honest information on most of the phenotypic conditions tested, whereas the pheromone amount in the glands provided an honest signal of quality for extreme phenotypes only. Moreover, males used the information conveyed by the female pheromone to choose their mates, approaching females that signaled higher reproductive potential. In addition, when simulating the female effect, using the synthetic pheromone blend that represents higher quality females (0.6:0.4 ZZ:ZE), more males were attracted to this blend than to the blend representing the population mean (0.5:0.5 ZZ:ZE). Both, female advertisement for males and the male choosiness, suggest that pheromones have evolved as sexual traits under directional, sexual selection. We suggest that the pheromone blend may serve as a multicomponent signal whereby each component adds information concerning the current condition of the female, and all are necessary to elicit a mate searching response. Abstract : Most studies of mate choice focus on females choosing males, based on traits that indicate their quality. This study demonstrates that male moths choose females based on their pheromone characteristics. The pheromone reflects the female's body size, her age and nutrition level, which in turn reflects the female's lifetime fecundity. Thus, males that choose females based on the information in their pheromone also choose females that are more fecund.